IMPLEMENTASI ALGORITMA KOMPRESI PADA STEGANOGRAFI CITRA DIGITAL DENGAN METODE MODIFIKASI LSB - Andi Setiadi Manalu (Politeknik Bisnis Indonesia, 2018)
Steganography technique using the LSB (Least Significant Bit) modification method is the simplest technique. Therefore steganography with this method is very suitable for beginners in the field of steganography. The LSB modification method stores data by replacing insignificant bits in the file cover with the bits of the file to be stored. One of the weaknesses of modified LSB method is its inability to store large size data. On average, the steganography technique with the modified LSB method is only able to store data in the size of one eighth of the size of the cover (for the cover in the form of 24-bit image), of course this is not efficient. To overcome this problem, in this research several methods were proposed to enlarge the capabilities of the modified LSB steganography technique in storing data. The first method is preprocessing the data files to be stored, namely by compression the data, the second is to prepare the file cover (stretch) by enlarging the file cover (stretching image), and the third is combining the first method and second at the same time. In this research, an analysis of the processes and results of each method will also be carried out. To increase the security of the data to be stored, the data stored is also encrypted first.